Does knowledge intensity of industry promote firm's ICT use?: empirical evidence from South Korea - Won, Jeong Yeon; Park, Min Jae (International Journal of Business Information Systems, 2021)
This paper investigates the factors that influence the digital divide at a corporate level and the effects that external factors (transaction and knowledge intensity of industries) have over the division of company levels. The conceptual framework of this study is based on a theory of planned behaviour (TPB) model to explain the gap between the utilisation of ICT use in companies with a quantitative approach, by collecting a data sample of 4,303 Korean companies participated in national survey of 2016. There exist endogenous factors such as perception of using value, management support and innovation readiness to influence the use of ICT. In addition, the moderating effect of knowledge intensity of industries (KII) has a limited impact on the ICT use. This paper aims to examine the digital divide with an extension of changes from corporations to the industrial structures.
Keywords: Digital divide; Firm-level; ICT use; Knowledge intensity; South Korea; Theory of planned behaviour; TPB